Fatores que influenciam a distribuição da herbácea Heliconia acuminata L. C. Rich (Heliconiaceae) em subosque na Amazônia central - Rubim, Paulo (Universidade Federal de São Carlos, 2014)
The determinants of species distribution are continually questioned by researchers. What we know is that depending on the scale of approach such patterns may respond with different magnitudes. We did three approaches with different experimental designs with a common understory plant specie in central Amazonia. In the first chapter, we tested for the density-dependece on growth and mortality of seedlings. The results indicate that seedlings can grow less when alone in the natural environment, however, not observed experimentally. The second chapter, we describe the effects of neighborhood in reproductive effort. The reproductive frequency and intensity proved inconsistent spatially and temporally, the light was best explained the variation between neighborhood effects. And finally we explore the explanatory factors on Heliconia acuminata L. C. Richard (Heliconiaceae), distribution in mesoscale and landscape scale. The mechanims approach on a landscape scale becomes less representative by soil components distribution associated with altimetry in landscape set distribution patterns. The seedling emergence spatial pattern overlaps with the density in breeding and reproductive individuals, increase in occupancy around these individuals, independent of sample scale. In this scenario, we analized the density-dependence effects, neighbor effects and explanatory factors on H. acuminata in the three following chapter.
Keywords: Plantas; Plantas - reprodução; Amazônia central; Ecologia; Heliconia acuminata; CIENCIAS BIOLOGICAS::ECOLOGIA